What Do We Really Know About Real Exchange Rates? - Ronald Mac Donald (Oesterreichische Nationalbank (OeNB), 1998)
This paper seeks to provide a comprehensive overview of the recent literature on the economics of real exchange rates. In particular, the paper attempts to provide answers to the following questions: to what extent are real exchange rates mean reverting and how may the degree of observed mean reversion be explained?; do real exchange rates have a business cycle component and, in particular, are they related to real interest differentials?; how important are real, relative to nominal shocks, in driving real exchange rates?; is the systematic component of the real exchange rate related to factors such as productivity, net foreign asset accumulation, national savings imbalances and terms of trade effects?
Keywords: F31; E30; 330; Real Exchange Rates; Mean Reversion